EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN ROLE PLAYING DALAM MENUMBUHKAN SIKAP DEMOKRATIS SISWA PADA MATA PELAJARAN PKN DI SD GMIT KUANINO 3 - Celline; Erlin Liunokas; Nelci Nobrihas; Jimylton Dethan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to test the effectiveness of the Role Playing learning model in fostering democratic attitudes in students in Civics (PKn) in elementary schools. This study employed a quantitative approach with a one-group pre-experimental design (One Group Pretest-Posttest Design). The subjects were 11 fifth-grade students of GMIT Kuanino 3 Elementary School. Data were collected using a Likert-scale democratic attitudes questionnaire and analyzed using descriptive and inferential statistics. The descriptive analysis showed an increase in the average score of students' democratic attitudes from 43.00 (Agree) in the pretest to 47.05 (Strongly Agree) in the posttest, representing a 9.88% increase in effectiveness. This increase was confirmed by the results of the Paired Sample T-Test, which yielded a t-value of -5.750 with 10 degrees of freedom (df) and a p-value of 0.000. Because the p value <0.05, it is proven that there is a significant difference between the scores before and after the intervention. It is concluded that the implementation of the Role Playing learning model is significantly effective in fostering democratic attitudes in fifth grade students of GMIT Kuanino 3 Elementary School. Keywords: Role Playing learning model, democratic attitude